Towards the Development of an Integrative, Evidence-based Suite of Indicators for the Prediction of Outcome Following Mild Traumatic Brain Injury - Gozt, Aleksandra Karolina (Curtin University, 2021)
This thesis focuses on identifying factors that could be used to predict recovery following concussion. The first study is a pilot assessment of blood-based biomarkers, neuropsychological tests and MRI outcomes, followed by a protocol paper for a large scale clinical study designed to identify predictive indicators. The thesis features three journal publications, one of which is a seminal review article on a novel neuroimaging analysis technique called Quantitative Susceptibility Mapping.